Studi Literature: Cara Menurunkan Hipertensi Dengan Latihan Fisik - Nurhidayah Amir; Rifki Sakinah Nompo; Angela L Thome; Yuliana Done; Viertianingsih Patungo; Fathia Fakhri Inayati Said (Universitas Malahayati Lampung, 2022)
ABSTRACT: LITERATURE STUDY: HOW TO REDUCE HYPERTENSION WITH PHYSICAL EXERCISE Background: Hypertension is high blood pressure which is divided into three levels, namely pre-hypertension, first-degree hypertension and second-degree hypertension. Hypertension is also dubbed the silent killer because most of the causes are unknown, where the symptoms that arise vary in each individual and these symptoms are similar to the symptoms of other diseases. Symptoms of hypertension include: heaviness in the neck, headaches, heart palpitations, blurred vision, ringing in the ears, fatigue, vertigo, and nosebleeds. Objective: This study aims to determine physical exercise in lowering blood pressure in hypertensive patients. Methods: This research is a literature study research. The data in this study were obtained from three databases, namely Google Scholar, Garuda and PubMed with the keywords